Elucidating spray-dried dispersion dissolution mechanisms with focused beam reflectance measurement: contribution of polymer chemistry and particle properties to performance. (21st October 2019) - Rawlinson-Malone, Clare Frances; Ferreira, Ana Patricia; Nicholls, Daniel; Nicholson, Sarah
Abstract: Amorphous spray-dried dispersions (SDDs) are a key enabling technology for oral solid dosage formulations, used to improve dissolution behaviour and clinical exposure of poorly soluble active pharmaceutical ingredients (APIs). Appropriate assessment of amorphous dissolution mechanisms is an ongoing challenge. Here we outline the novel application using focused beam reflectance measurement (FBRM) to analyse particle populations orthogonal to USP 2 dissolution. The relative impact of polymer substitution and particle attributes on 25% BMS-708163/HPMC-AS SDD dissolution was assessed. Dissolution mechanisms for SDDs were categorized into erosion versus disintegration. Beyond an initial mixing period, FBRM particle counts diminish slowly and particles are detectable until the point where API dissolution is complete. There is correlation between FBRM particle count decay rate, representing loss of SDD particles in the dissolution media, and UV dissolution rate, measuring dissolved API. For the SDD formulation examined, the degree of succinoyl substitution for HPMC-AS, SDD particle size and surface area all had an impact on dissolution. These data indicate the SDD displayed an erosion mechanism and that FBRM is capturing a rate-limiting step. From this screening tool, the mechanistic understanding and measured impact of polymer chemistry and particle properties can inform a risk-assessment and control strategy for this compound. Abstract :